THE ROLE OF TAX AMNESTY AS A MODERATION OF TAX SANCTIONS AND TAXPAYER AWARENESS TOWARDS TAXPAYER COMPLIANCE IN UMKM IN LUMAJANG REGENCY - NUGROHO, FERDIAN; NASTITI, ARI SITA; SYAHFRUDIN ZULKARNNAENI, ACHMAD (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the influence of tax sanctions, taxpayer awareness, and the Tax Amnesty program on the tax compliance of MSMEs in Lumajang Regency, as well as to examine the moderating role of Tax Amnesty in these relationships. The research method used is quantitative with a moderated regression analysis (MRA) approach. Data were collected through questionnaires distributed to 99 MSME respondents. The results show that tax sanctions and taxpayer awareness have a significant effect on tax compliance. Tax Amnesty also significantly affects tax compliance and is able to moderate the relationship between tax sanctions and tax compliance. However, Tax Amnesty does not significantly moderate the relationship between taxpayer awareness and tax compliance. These findings emphasize that strict sanctions and high awareness are the main factors driving taxpayer compliance. Meanwhile, the Tax Amnesty program can strengthen the effect of sanctions but is less effective when linked to taxpayer awareness. This study provides important implications for policymakers to strengthen sanction mechanisms and improve tax education among MSME actors.